2001
DOI: 10.1094/cchem.2001.78.3.226
|View full text |Cite
|
Sign up to set email alerts
|

Effect of l‐Cysteine on the Rheological Properties of Wheat Flour

Abstract: Cereal Chem. 78(3):226-230Extrudate expansion of cereal-based products is largely dependent on the molecular interactions and structural transformations that proteins undergo during extrusion processing. Such changes strongly influence the characteristic rheological properties of the melt. It is possible to modify rheological properties of wheat flour during extrusion processing, in particular shear viscosity, with cysteine. The objective of this work was to further develop an understanding of the molecular in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 17 publications
1
17
0
1
Order By: Relevance
“…In pasta, it has been shown that the gluten fraction containing LMW-GS are the primary contributors to mechanical strength in the cooked product (Resmini and Pagani, 1983). It is worth noting that cysteine's mobility was likely not restricted in our low-moisture system as cysteine has been found to be rheologically active in a study that had used wheat doughs with a 25% moisture content (Lambert and Kokini, 2001). It can therefore be argued that cysteine was indeed of value to alter the rheological behaviour of YAN, despite its low-moisture content.…”
Section: Effect Of Cysteine On Noodle Rheological Behaviourmentioning
confidence: 93%
See 1 more Smart Citation
“…In pasta, it has been shown that the gluten fraction containing LMW-GS are the primary contributors to mechanical strength in the cooked product (Resmini and Pagani, 1983). It is worth noting that cysteine's mobility was likely not restricted in our low-moisture system as cysteine has been found to be rheologically active in a study that had used wheat doughs with a 25% moisture content (Lambert and Kokini, 2001). It can therefore be argued that cysteine was indeed of value to alter the rheological behaviour of YAN, despite its low-moisture content.…”
Section: Effect Of Cysteine On Noodle Rheological Behaviourmentioning
confidence: 93%
“…The sulfhydryl groups (-SH) of cysteine are thought to reduce dough strength by promoting cleavage of intermolecular disulfide bonds and/or by increasing the rate of disulfide-sulfhydryl exchange reactions (McDermott and Pace, 1961). Stress relaxation tests are sensitive to the protein depolymerization effects of cysteine on a wheat flour dough because the changes that could be induced (i.e., changes in molecular weight or conformational structural changes) are intimately related to the rheology of the dough (Dreese et al, 1988;Lambert and Kokini, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Cysteine cleaves disulfide bonds, resulting in increased protein solubility and decreased gluten elasticity (Li & Lee, 1998). Increasing cysteine content in flour has been shown to adversely affect dough rheology by cross links breakage as evident by decrease in storage modulus (G 0 ) values (Lambert & Kokini, 2001). Removing those reducing agents from the enzyme mix by dialysis resulted in stronger dough with strength that was comparable to the control (Fig.…”
Section: Mixing Behavior Of Enzyme-treated Floursmentioning
confidence: 93%
“…It is reported that wheat flour contains non-protein thiol compounds or free thiols like glutathione (GSH) and cysteine and they have been considered to play an important role in redox reactions in flour. Content of free thiols like GSH and cysteine was reported to influence the rheological and bread properties of flour [50][51][52][53].…”
Section: Effect Of Reconstitution On Rheological Characteristics and mentioning
confidence: 99%